2015
DOI: 10.5114/ceji.2015.56961
|View full text |Cite
|
Sign up to set email alerts
|

Matrine improves cognitive impairment and modulates the balance of Th17/Treg cytokines in a rat model of A β1-42 -induced Alzheimer’s disease

Abstract: Matrine (MAT) has been reported for its anti-inflammatory and neuroprotective effects. However, little is known about its effects on Th17/Treg cytokines and cognitive impairment in Alzheimer's disease (AD). In the present study, we injected Aβ1-42 to the hippocampus of the rat to induce AD. Three groups of the AD rats were treated with MAT (25, 100 or 200 mg/kg/day, respectively) by intraperitoneal injection for 5 weeks. Levels of Th17 cell cytokines [interleukin (IL)-17A and IL-23] and regulatory T (Treg) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…administration ameliorated Aβ‐like symptoms (in terms of olfactory dysfunction, spatial and working memory) both after 7 and 14 days, similar to that observed after a double IL‐17Ab IN administration on days 5 and 12. The difference in terms of time of administration is justified by earlier observations that found a significant increase of Th17 cytokines following 7 days from Aβ injection (Zhang et al, ; Zhang et al, ). Moreover, very robust effects were observed when the Ab was administered at dose of 1 μg·μl −1 , compared with the isotype Control or Ab itself, consistent with previous in vivo reports (Fischer et al, ; Mi et al, ; Szabo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…administration ameliorated Aβ‐like symptoms (in terms of olfactory dysfunction, spatial and working memory) both after 7 and 14 days, similar to that observed after a double IL‐17Ab IN administration on days 5 and 12. The difference in terms of time of administration is justified by earlier observations that found a significant increase of Th17 cytokines following 7 days from Aβ injection (Zhang et al, ; Zhang et al, ). Moreover, very robust effects were observed when the Ab was administered at dose of 1 μg·μl −1 , compared with the isotype Control or Ab itself, consistent with previous in vivo reports (Fischer et al, ; Mi et al, ; Szabo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of Th17 transcription factor RORγt, in addition to IL-17 and IL-22, have been found in the brains of animal models of AD (Zhang, Ke, Liu, Qiu, & Peng, 2013;Zhang, Liu, Sun, & Yin, 2015) and the increase of Th17/IL-17A axis is sustained by Aβ-induced oxidative stress (Solleiro-Villavicencio & Rivas-Arancibia, 2017). Furthermore, Zenaro et al (2015) showed a role for neutrophils in AD-like pathogenesis and cognitive impairment through the release of neutrophil extracellular traps and IL-17 into the brain, suggesting that the inhibition of neutrophil trafficking and related neuro-inflammatory onset may be beneficial in this pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In 5XFAD mice, another animal model of AD, the production of IL-17A is decreased in the gut-residing immune cells (Saksida et al, 2018 ). In another animal models of AD including hAPP mice, 3xTg-AD mice, Mo/Hu APPswe PS1dE9 mice and Aβ1–42-Induced AD rat model, the level of IL-17A shows a significant upregulation compared with wild type mice (Jin et al, 2008 ; Zhang et al, 2013 ; Zhang Y. et al, 2015 ; Chen et al, 2015 , 2019 ; Yang et al, 2015 ; St-Amour et al, 2019 ). In MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) treaded mouse and MPP+ (1-methyl-4-phenylpyridinium) treated rats (animal models of PD), the levels of IL-17A are upregulated in the substantia nigra, spleen, serum, and mesenteric lymph nodes.…”
Section: The Role Of Il-17a In a Different Model System Of Neurodegenmentioning
confidence: 99%
“…Matrine was considered in our study because of knowledge that it had promoting effects on the PI3K/Akt/mTOR signaling in brain ( Liu et al , 2017 ), while mTOR is closely involved in the pathophysiology of depression ( Abelaira et al , 2014 ). Besides, previous studies have demonstrated that matrine has protecting and improving effects on neuropathic pain, Alzheimer’s disease, and Parkinson’s disease ( Zhang et al , 2015 ; Gong et al , 2016 ; Meng et al , 2017 ). These reports may also imply the antidepressant-like actions of matrine, as these neurological disorders are always accompanied with depression ( Li et al , 2014 ; Goto et al, 2018 ; Laumet et al , 2017 ; Sampath et al , 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Gong et al reported that matrine had neuroprotective effects on a mouse model of vincristine-induced neuropathic pain ( Gong et al , 2016 ). Zhang et al showed that matrine improved cognitive impairments in a rat model of Alzheimer’s disease ( Zhang et al , 2015 ). Meng et al showed that matrine also had neuroprotective effects against MPTP-induced Parkinson’s disease ( Meng et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%